Studi Tingkat Pengetahuan Diabetes Antara Penderita Diabetes dan Non-Diabetes di Puskesmas Brondong, Lamongan - Almas Ula Salsabila; Rivan Virlando Suryadinata; Theresia Desy Askitosari; Panjumi Khorida (Jurnal Kesehatan Komunitas, 2022)
Diabetes mellitus is a disease with hyperglycemia in the body. Various complications arising from diabetes mellitus can interfere with the quality of life of sufferers. Knowledge about diabetes is very necessary for diabetics. It is hoped that this will raise awareness for diabetics to adopt a healthy lifestyle so diabetics can carry out therapy properly to prevent and reduce the impact of complications caused by diabetes mellitus. This study aims to see the level of knowledge about diabetes among diabetics at Puskesmas Brondong, Lamongan. The research method used a case-control study which was divided into the diabetic group and the non-diabetic group. The sample size in each group was 50 people and was carried out by purposive sampling. The results showed that there was a significant difference in the knowledge level of diabetes between the second group (p = 0.000) and had a strong association (r = 0.578). This study concluded that the diabetic group has a knowledge level of diabetes better than the non-diabetic group at Puskesmas Brondong, Lamongan.